Investigation on Families Have Autistic Children About Knowledge Level of Vaccines, Vaccination Denial Frequency, and Reasons of Vaccination Denial in Different Regions of Turkey - Keşli, R.; Dünya, Y.; Zaheer, A.; Roudkoli, D.R.; Gün, R.; Bardak, M.; Yücesan, E.Z. (Selcuk University, 2021)
Objective: Autism spectrum disorder (ASD) is an important neurodevelopmental disorder, that manifests itself in the decline of the social interaction and communication, learning, and language skills in early childhood. The aim of this study was to measure the general knowledge of the parents have children diagnosed with ASD, to determine their attitudes towards vaccination, to determinate the rate and reason of anti-vaccination. Material and Methods: The study was carried out by conducting a survey, by means of talking face to face one of ASD diganosed children’s parents. Results: According to the data obtained, when compared to the control group’s and ASD parents; have higher level of knowledege about vaccines, and preference of vaccination refusal, have higher rate of doubt related with Ingredients of vaccines, and believe that; there was a temporarly connection between onset of autism, and especially live viral vaccines. Conlcusion: Thoughts, worries, and drawbaks of the families should be evaluated during the routine control of cihildren dignosed as ASD, by child and adolescent psychatrists. © 2021, Selcuk University. All rights reserved.
Türkiye’nin Farklı Bölgelerinde Otizmli Çocuğu Olan Ailelerin Aşılar Hakkındaki Bilgi Düzeylerinin, Aşı Reddinin Sıklığının ve Nedenlerinin Araştırılması
Keywords: Autism Spectrum Disorder; Etiology; Knowledge Level; Vaccination Refusal Frequency; Vaccines